A case‐based discussion of clinical problems in the management of patients treated with ruxolitinib for myelofibrosis. Issue 3 (March 2017) - Ho, P. Joy; Bajel, Ashish; Burbury, Kate; Dunlop, Lindsay; Durrant, Simon; Forsyth, Cecily; Perkins, Andrew C.; Ross, David M.
Abstract : Ruxolitinib is a dual janus kinase 1 (JAK1)/JAK2 inhibitor used to treat splenomegaly and symptoms associated with myelofibrosis (MF). Current therapeutic options for symptomatic MF include supportive care, myelosuppressive therapy (such as hydroxycarbamide) and janus kinase (JAK) inhibitors (in particular ruxolitinib). Allogeneic stem cell transplantation remains the only potentially curative treatment for MF, and younger transplant‐eligible patients should still be considered for allogeneic stem cell transplantation; however, this is applicable only to a small proportion of patients. There is now increasing and extensive experience of the efficacy and safety of ruxolitinib in MF, both in clinical trials and in 'real‐world' practice. The drug has been shown to be of benefit in intermediate‐1 risk patients with symptomatic splenomegaly or other MF‐related symptoms, and higher risk disease. Optimal use of the drug is required to maximise clinical benefit, requiring an understanding of the balance between dose‐dependent responses and dose‐limiting toxicities. There is also increasing experience in the use of ruxolitinib in the pre‐transplantation setting. This paper aims to utilise several 'real‐life' cases to illustrate several strategies that may help to optimise clinical practice.